Virtual patient clinical placements improve student communication competence - Robinson, K.; Allen, Peter; Quail, M.; Beilby, Janet (Routledge, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Effective communication is a generic competency essential to clinical practice. However, access to work-integrated placements where such competencies are traditionally developed is diminishing, compelling universities to develop supplementary placement opportunities in the form of simulated learning environments (SLE). Virtual or digital patient (VP) placements are an attractive SLE model, but evidence of their efficacy for developing student communication competence is limited. In the current study, 82 second-year undergraduate speech pathology students completed one half-day placement, requiring them to use conversation interaction skills to build rapport with a VP across two 10-minute interactions, separated by clinical educator (CE) feedback and self-reflection. Each student’s interactions were rated by CEs on 25 communication competencies and, following the second interaction, students completed retrospective pre-placement and post-placement self-ratings of their communication skills, knowledge and confidence. CEs’ ratings of students’ performance were significantly higher following the second interaction than they were following the first (median h2p =.710). Furthermore, the students’ post-placement self-ratings were significantly higher than their retrospective pre-placement ratings (median dav = 1.25). These findings suggest that VP placements as simulated clinical learning opportunities support speech pathology education, and may have positive implications for all health professions.